Stages of change in physical activity, self efficacy and decisional balance among Saudi university students - Ensaf S.A. Gawwad (Wolters Kluwer Medknow Publications, 2008)
Background : Determining the stages of change in physical activity (PA) helps to determine effective promotion of PA interventions. The aim of the study was to assess the readiness of students of King Saud University (KSU) to be more physically active and relate this to their self efficacy, perceived benefits and perceived barriers to PA. Method : A cross-sectional descriptive study was conducted at KSU, Riyadh, between March and May 2007, using a self-administered questionnaire. The total sample size was 302 randomly chosen male and female students. Results : More than half of the students (55.3%) reported that they participated in PA in the action (for <6 months) and maintenance (for > 6 months) stages. The remaining students did not engage in PA as they were in precontemplation, contemplation, preparation and relapse stages. More males were found in the maintenance stage, but more females were found in the inactive stages (precontemplation, contemplation and preparation). Only 24.4% of the students were engaged in PA as much as three times or more/week and 9.9% engaged in PA regularly through out the year. About 39% of which, significantly, more were males did vigorous PA for 20 minutes or more. However, 4.6% described themselves as hyperactive. More females used the stairs, did house work and considered themselves moderately active. Nearly 50% had a low total score of perceived barriers while 85% had high perceived benefits and 63.6% had moderate self efficacy of PA. The main barriers perceived were time and resources. The score relating to barriers decreased significantly across stages of change, but the pattern was reversed with regard to the perceived benefits and self-efficacy (p<0.05). Conclusion : Physical inactivity is common among KSU students. A considerable proportion of them was not ready to become more physically active. The study highlights the need to adapt PA promotion programs to states of readiness for PA. University and public policies as well as environmental changes are necessary to encourage active living within the context of Islamic rules and Saudi culture.